MEDIATING INTELLECTUAL CAPITAL ON DIGITAL MARKETING FOR MARKETING PERFORMANCE IMPROVEMENT OF COPPER-BRASS CREATIVE INDUSTRY SMEs - Yuni Pambreni; Udriyah Udriyah; Dwi Rachmawati (LPPM Universitas Sangga Buana, 2023)
This study used path analysis as research method to analyze the mediating of intellectual capital variable on digital marketing for marketing performance improvement of copper-brass creative industry SMEs in Tumang, Boyolali as the center of copper-brass creative industry in Indonesia. Digital marketing as independent variable with indicators which are cost, incentive program, site design, and interactive. Intellectual capital as intervening/mediating variable with indicators, human capital, organizational capital, and social capital. Then, marketing performance as dependent variable with measuring indicators are sales volume, customer growth, and revenue growth. Primary data was obtained by questionnaire as research instrument, then the data was processed with SPSS 23.0. Population in this study is copper-brass creative industry SMEs in Tumang, Cepogo, Boyolali. The sample size is 99 manpower respondents, either owner or employee. The result of this study indicate that Copper-brass creative industry SMEs can improve and optimize marketing performance by rising digital marketing which will affect the increasing of intellectual capital and marketing performance.